An institutional approach to vulnerability: evidence from natural hazard management in Europe. (8th April 2021) - Papathoma-Köhle, M; Thaler, T; Fuchs, S
Abstract: Institutional vulnerability to natural hazards has not been thoroughly investigated until now. Yet, institutional vulnerability is strongly connected to all other vulnerability dimensions, and specific socio-economic and physical indicators. Moreover, different types of crises such as economic, political or health crisis strongly affect the institutional capacity of communities to deal with the consequences of natural hazards. For this reason, a deep insight to the institutional dimension of vulnerability is needed in order to reduce disaster risk under the effects of climate but also socio-economic change. In the present paper, institutional vulnerability is defined and its main pillars and drivers are identified. A framework is presented showing the interactions between the drivers of institutional vulnerability and the indicators of other vulnerability dimensions (physical, social, economic, cultural and environmental). The interactions between institutional vulnerability and other vulnerability dimensions are highlighted through three European case studies: Greece, the United Kingdom and Austria. The case studies show how current issues such as the recent financial crisis and Brexit, may directly influence the drivers of institutional vulnerability and consequently all other vulnerability dimensions. The framework and the case studies clearly indicate that institutional vulnerability is an 'umbrella' dimension strongly related to all other dimensions and has to be approached as such in order to reduce vulnerability and, consequently, disaster risk.